SOCIAL AND CULTURAL CHAOS IN INDIAN WOMEN LIFE WITH REFERENCE TO VIRANI PINKI SELECTED NOVELS - KUMAR, PYLA RAVI; KUMAR, PYLA RAVI (International Journal of Psychosocial Rehabilitation, 2020)
Women who constitute half of the world’s population are paradoxically not treated on par  with men in all spheres of human activity. They are oppressed, suppressed and marginalised  in the matter of sharing the available opportunities for fulfilment of their lives, despite the  fact that every woman slaves for the development of her family, her husband and children.  This disturbing picture of woman is not something new or unique only to India.